Exclusão e formação na instituição escolar pública - Torman, Ronalisa (Universidade do Vale do Rio do Sinos, 2006)
This dissertation demonstrates the relation among the social exclusion, the stigma and the psychological suffering generated by the social exclusion, from the analysis of the public school institution and the formative process on daily life. The importance of this study is based on understanding of the social interaction established on daily life, on the construction of new concepts and practices concerning to formation and on the trajectory of the students inserted in the school institutions. The current job investigates the role of the school institution by means of development of the formation and the knowledge, through critical perspective and by means of approach qualitative and quantitative. It was chosen to make a study as descriptive research form that allowed the notice and assessment of the relation among the variables in question. Thereby, it was carried out interviews with administrators of two public schools that had on base a schedule composed of open questions for free answer from the interview
Keywords: estigma; exclusão social; formação; instituição escolar; sofrimento; formation; school institution; social exclusion; stigma; suffering; Ciências Sociais Aplicadas